A novel SIRT6 activator ameliorates neuroinflammation and ischemic brain injury via EZH2/FOXC1 axis - Tailin He; Jialin Shang; Chenglong Gao; Xin Guan; Yingyi Chen; Liwen Zhu; Luyong Zhang; Cunjin Zhang; Jian Zhang; Tao Pang (Elsevier, 2021)
Ischemic stroke is the second leading cause of death worldwide with limited medications and neuroinflammation was recognized as a critical player in the progression of stroke, but how to control the overactive neuroinflammation is still a long-standing challenge. Here, we designed a novel SIRT6 activator MDL-811 which remarkably inhibited inflammatory response in lipopolysaccharide (LPS)-stimulated RAW264.7 macrophages and primary mouse microglia, which were abolished by silencing SIRT6. RNA-seq screening identified the forkhead box C1 (Foxc1) is a key gene evoked by MDL-811 stimulation and is required for the anti-inflammatory effects of MDL-811. We found MDL-811-activated SIRT6 directly interacted with enhancer of zeste homolog 2 (EZH2) and promoted deacetylation of EZH2 which could bind to the promoter of Foxc1 and upregulate its expression to modulate inflammation. Moreover, our data demonstrated that MDL-811 not only ameliorated sickness behaviors in neuroinflammatory mice induced by LPS, but also markedly reduced the brain injury in ischemic stroke mice in addition to promoting long-term functional recovery. Importantly, MDL-811 also exhibited strong anti-inflammatory effects in human monocytes isolated from ischemic stroke patients, underlying an interesting translational perspective. Taken together, MDL-811 could be an alternative therapeutic candidate for ischemic stroke and other brain disorders associated with neuroinflammation.